Victimization mechanisms and countermeasures in telecom network fraud: a dual-system theoretical perspective - Xu, Fuming; Liu, Anning; Li, Xinjing (Frontiers in Psychology, 2025)
Despite individuals’ awareness of the risks associated with fraud, they frequently engage in irrational decision-making within the realm of telecom network fraud, revealing a dissonance in their cognitive information-processing systems. This paper leverages dual-system theory and the three-stage dual-process model to scrutinize the cognitive trajectories of victims, accentuating the heuristic biases driven by System 1, alongside the ineffective intervention by System 2. Furthermore, it introduces a novel framework that maps “Cognitive Bias, Fraud Type, and Countermeasures.” The study underscores the combined impact of individual characteristics and situational variables in influencing the operation of both cognitive systems, providing insights for the cognitive design of targeted fraud prevention strategies.